Child malnutrition in Mexico in the last two decades: prevalence using the new WHO 2006 growth standards Malnutrición preescolar en México en las últimas dos décadas: prevalencias usando los estándares de la OMS-2006 - Teresa González-de Cossío; Juan A Rivera; Dinorah González-Castell; Mishel Unar-Munguía; Eric A Monterrubio (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To describe preschool malnutrition prevalence and trends in Mexican children for the 1988, 1999 and 2006 Mexican National Nutrition Surveys using WHO-2006 standards and National Center for Health Statistics/WHO (NCHS/WHO) references. MATERIAL AND METHODS: Prevalence of undernutrition (< minus 2 z-score for weight/age, height/age and weight/height) and overweight (> plus 2 z-score for weight/height) were calculated. RESULTS: Height/age and weight/height have increased over time (p< 0.05). Using WHO-2006 standards, stunting in children less than 5 years years old was 26.9%, 21.5% and 15.5% in 1988, 1999 and 2006, respectively; values for wasting were 6.2%, 2.1% and 2.0%, respectively. Wasting in the very young (< 6 mo) in 2006 is high (4.9%). Overweight increased from 1988 to 1999 (6.1% to 7.5%) and stabilized in 2006 (7.6%). Gaps among ethnic and socioeconomic groups have decreased over time. CONCLUSIONS: Stunting has decreased markedly but continues to be the main malnutrition problem. Overweight has emerged as a public health problem in the young. Lower NCHS/WHO estimates previously published underestimated true prevalence. Length deviations in attained height after 12 months indicate poor infant feeding practices, probably coupled with early infections. Results reinforce the need to improve the quality of nutrition programs and to promote adequate lactation and infant feeding practices in Mexico. OBJETIVO: Describir las prevalencias y tendencias de malnutrición en preescolares mexicanos, según resultados de las Encuestas Nacionales de Nutrición 1988, 1999 y 2006, usando estándares de la Organización Mundial de la Salud de 2006 y referencias del National Center for Health Statistics/ World Health Organization (NCHS/WHO). MATERIAL Y MÉTODOS: Se calcularon prevalencias de desnutrición (puntaje z < -2 para talla/edad, peso/edad, y peso/talla) y de sobrepeso (> +2z peso/talla). RESULTADOS: La talla/edad y el peso/talla han aumentado con el tiempo (p< 0.05). Usando los estándares de la OMS de 2006, el desmedro en menores de cinco años de edad era de 26.9, 21.5 y 15.5% en 1988, 1999 y 2006, respectivamente. Los valores de emaciación fueron 6.2, 2.1 y 2.0%. La emaciación en 2006 en los menores de seis meses de edad fue de 4.9%. El sobrepeso aumentó de 1988 a 1999 (6.1 a 7.5%) y se estabilizó en 2006 (7.6%). Las diferencias entre grupos étnicos y socioeconómicos disminuyeron con el tiempo. CONCLUSIONES: El desmedro disminuyó marcadamente, pero continúa siendo el principal problema de malnutrición. El sobrepeso emergió como problema de salud pública en niños. Las estimaciones de desnutrición en preescolares previamente publicadas usando las referencias del NCHS/WHO subestimaban las verdaderas cifras. Las desviaciones en la talla alcanzada a partir de los 12 meses de edad revelan prácticas de lactancia y alimentación infantil pobres, probablemente aunadas a infecciones tempranas. Estos resultados refuerzan la necesidad de mejorar la calidad de los programas de nutrición y de promover prácticas adecuadas de alimentación infantil en México.